El proceso de recepción del decreto conciliar «Optatam totius» en las «Ratio» de la Iglesia Latinoamericana - Mauti, Ricardo Miguel (Estudios eclesiásticos, 2023)
The conciliar decree Optatam totius on priestly formation represented an enormous challenge for the entire Church and particularly for Latin America. Many advice and wishes of the Latin American bishops during the Council were expressed in it, concerned with the renewal of the formation of future priests, in accordance with the new challenges of the time. The Council gave the Episcopal Conferences a mandate of permanent value, to draw up their own Ratio nationalis and to update them from time to time. The present study addresses this process of reception in various Ratio of Latin America, seeking to highlight how the notion of creative fidelity was assumed in all the breadth desired by the Council and opens a critical balance of future perspectives.